A39 REDUCED ERYTHROPHAGOCYTOSIS IN MUC2 DEFICIENT MICE IS SUSCEPTIBLE TOWARDS LPS INDUCED SEPSIS. (15th March 2019) - Kumar, M; Moreau, F; Chadee, K
Abstract: Background: Intestinal mucus separates gut microbiota and its components from host tissue and any perturbation in mucus layer integrity is associated with local as well as systemic inflammation. Inflammatory bowel disease (IBD) patients have an altered mucus layer with impaired host defenses and are high risk for developing sepsis. Iron maintains inflammatory homeostasis and iron metabolism dysregulation is the most common extra intestinal problem in IBD. Here, we used Muc2 mucin deficient ( Muc2 -/- ) mice, which exhibit basal low-grade inflammation due to increased bacterial penetrants and is an excellent model to study chronic colitis. We hypothesize dysregulated iron homeostasis impairs host defense against inflammatory challenges. Aims: To assess the effect of dysregulated iron homeostasis on innate host defense using LPS induced septic shock. Methods: Red blood cells (RBCs) from 6–8 weeks old Muc2 -/- and Muc2 +/+ littermates were stained with a lipophilic dye and injected intravenously. 16 h post RBCs transfer, animals were euthanized and single cell suspension of splenocytes were stained with F4/80 and TER119 antibodies to determine RBCs clearance by Flow cytometry. Anti-mouse AF647-F4/80 antibodies were used to visualize erythrophagocytosis in spleen via spinning disk confocal microscopy. Bone marrow chimeras of Muc2 genotypes were generated and reconstituted with bone marrow cells. To quantify bacteria in driving inflammation, antibiotic treated and germ-free mice were used. LPS (i.p.) induced septic shock was used to asses host defense and monitored for BW loss and mortality. Results: Basally, Muc2 -/- exhibited significantly higher levels of RBCs clearance from the circulation as compared to Muc2 +/+ littermates. This was associated with reduced levels of erythrophagocytosis by splenic macrophages. Notably, senescent RBCs in Muc2 -/- were clustered together and formed aggregates in the spleen. To rule out genotype changes, Muc2 -/- RBCs injected in Muc2 +/+ littermates and vice versa showed that macrophages in Muc2 -/- had reduced efficiency to clear Muc2 +/+ and Muc2 -/- RBCs. Bone marrow chimeras, antibiotics treatment and germ-free animal revealed that basal inflammation was due to intestinal bacteria penetrants in Muc2 -/- and not genetic changes that affected erythrophagocytosis of Muc2 -/- splenic macrophages. This deficiency resulted in higher circulatory iron that increased Muc2 -/ - susceptibility towards LPS induced septic shock and mortality. Conclusions: Microbial penetrants due to increased gut permeability in Muc2 -/ - affected splenic macrophages to recycle senescent RBC resulting in higher iron levels that compromise host defenses. This could potentially exacerbate septic shock and lead to mortality. Funding Agencies: CCC, CIHR